Epistemic communities and trust in digital contexts - Gaitán Torres, Antonio (Daimon Revista Internacional de Filosofia, 2024)
En este artículo se analliza el concepto de 'comunidad epistémica' usado por Karen Frost-Arnold en Who Should You Be Online? (OUP, 2023). La primera sección sitúa este concepto en el argumento general del libro. La segunda sección separa tres posibles sentidos de 'comunidad epistémica' - sistémico, agregativo y grupal - e integra esos sentidos en el argumento general desarrollado en WSYBO. La tercera sección se centra en el sentido que considero más problemático, el sentido grupal. Se argumenta que, aunque algunos grupos cerrados contribuyen a generar conocimiento dentro de una comunidad epistémica, esas ventaja opera dentro de un abánico de posibilidades bastante estrecho, limitado tanto por la posibilidad de estructurarse como un grupo excluyentes como por la possibilidad de conformar grupos que vician debates desde dinámicas de pertenencia grupal. This commentary focuses on the notion of ‘epistemic community’ and its role in underpinning the general argument that Karen Frost-Arnold presents in Who Should You Be Online? (OUP, 2023). The first section presents the general argument of WSYBO, outlining the general structure of the book and its central concepts. In the second section, three possible senses of ‘epistemic community’ are distinguished – systemic, aggregate and group-oriented. The third section explores tensions around a variety of group-oriented epistemic community. It will address two ways in which certain closed epistemic communities organized around a shared identity can deviate from the epistemic ideals that guide Frost-Arnold's project. Some enclosed epistemic communities can be organized around exclusionary dynamics. Other enclosed epistemic communities may organize and grant membership around debates or controversies, affecting the deliberative quality of those debates. The epistemic potential of closed epistemic communities organized around a shared identity depends largely on avoiding these two deviations.